Pengembangan Media Pembelajaran Pai Berbasis Mentimeter di MAN 01 Rejang Lebong - Nofita Sari; Nafaisul Mustajada; Aida Rahmi Nasution; Epa Kristina (Journal on Education, 2025)
This journal aims to enable Islamic Religious Education learning to be more advanced and developed so that learning becomes more effective and efficient. All educational institutions must be proactive, creative and productive in reading the phenomena that occur today. Therefore, the role of Mentimeter learning media is very important here, creating a good design as a foundation for the advancement of information and communication technology, as well as adding Islamic religious education learning activities with materials and skills and practicing religion including learning activities and mastery. However, we must also be able to use a technical approach with learning methods using this Mentimeter-based media. Furthermore, the researcher will provide information regarding the type of research to be conducted, the planned time for implementing the research, and the class that will be the subject of the research. The results achieved are the process of developing Mentimeter-based Islamic Religious Education learning media, starting from the initial identification stage or implementation of preliminary research to the final revision stage.